AKIBAT HUKUM PENDIRIAN LEMBAGA KEUANGAN MIKRO OLEH BADAN HUKUM KOPERASI - Noer, Zakiah (JURNAL MEDIA HUKUM DAN PERADILAN, 2018)
This research is underlined by the existence of cooperative business activities which collect and distribute funds over its members, and also to its non-members. In order to avoid the violation of the provisions in Act No. 25 Year 1992 about Cooperatives, cooperative has established a microfinance institution (MFI) which called as Cooperative MFI. The establishment of microfinance institutions causes the legal consequences on several aspects because of the different regulations between Cooperative and MFI according Act No. 25 Year 1992 about Cooperatives and Act No.1 Year 2013 about Microfinance Institutions.